Biblical Criticism in Early Modern Europe: Erasmus, the Johannine Comma and Trinitarian Debate - McDonald, Grantley (Cambridge University Press, 2016)
This book explores the explosive social and political implications of Erasmus' philological work on the Greek New Testament